Studi Literatur: Inovasi Media Pembelajaran IPA Terkini - GH, Muliana; Ruslan, Zuhrah Adminira (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research uses descriptive literature study research method to investigate the types of current Science learning media used and developed in the last five years. The research steps include collecting research articles related to the use of science learning media, recording the findings of the types of science learning media and theories contained in the research articles, and analyzing the findings. The data source used is secondary data, through a search on the Google Scholar page with the keyword "Science Learning Media". The results of data analysis show that there are 30 types of science learning media used and developed in the last five years. The learning media are then grouped into five groups of learning media types, namely audiovisual and digital media, manipulative and interactive media, print media, visual media, and interactive and presentation media. The conclusion of this study is that the use of science learning media tends to include audiovisual and digital technology, where learning videos, multimedia presentations, and interactive applications are the main choices in the use of science learning media.